Pengaruh Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Melalui Keputusan Penggunaan Jasa Travel pada PT Pacto Bali - Satria Wibawa, A. A. Ngurah Adi; Sedana Putra P, Komang Widhya (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the effect of promotion and service quality on customer satisfaction, with service usage decisions as a mediating variable at PT Pacto Bali. The background of this research stems from the increasingly intense competition in the travel service industry in Bali and the importance of understanding the factors that determine customer satisfaction. The study employs a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method, processed with SmartPLS version 4.0 software. The research sample consists of 120 respondents selected through purposive sampling, namely customers who have used PT Pacto Bali’s services within the past six months. The results of this study are expected to show that promotion and service quality have both direct and indirect effects on customer satisfaction through service usage decisions. The PLS-SEM approach allows the researcher to simultaneously assess relationships among variables in both the measurement model and the structural model. The findings of this research are expected to provide theoretical contributions to the development of marketing management science, particularly consumer behavior in the digital tourism industry, as well as practical implications for PT Pacto Bali in formulating digital media–based promotional strategies and enhancing service quality based on customer experience.